Risk factors for contrast-induced acute kidney injury (CI-AKI): protocol for systematic review and meta-analysis. Issue 8 (13th August 2019) - Liu, Yong; Liang, Xingcheng; Xin, Shaojun; Liu, Jin; Sun, Guoli; Chen, Shiqun; Cen, Xiaolin; Dai, Xiaohua; He, Yibo; Song, Feier; Liang, Yan; Hu, Yuying; et al.
Abstract : Introduction: Identifying the patients who are at risk for contrast-induced acute kidney injury (CI-AKI), which is defined as an increase in serum creatinine after exposure to contrast media, is a critical step in targeted prevention strategies. The absolute and relative importance of individual risk factors have not been systematically evaluated, let alone the new, controversial and modifiable risk factors of CI-AKI. Methods and analysis: On 1 July 2019, a search was performed on MEDLINE, Embase and the Cochrane Database of Systematic Reviews. We will perform a systematic review and meta-analysis to assess the important risk factors for developing CI-AKI, including those new, modifiable factors, which are considered controversial. The secondary endpoint will be all-cause mortality. Two authors will then independently screen studies that meet the criteria for inclusion, consulting with a third author to resolve any dispute. The quality of the included studies will be assessed according to the Newcastle-Ottawa scale. Ethics and dissemination: Ethics approval in this systematic review and meta-analysis protocol is not needed. We will disseminate the findings of this systematic review and meta-analysis via publications in peer-reviewed journals. PROSPERO registration number: CRD42019121534